Colour prediction as a weaving design selection help tool in Jacquard CAD - Miled, Wafa; Algamdy, Hind; Benltoufa, Sofien; Khan, Muhammad A. (Industria Textila, 2023)
The final colour prediction of a weave design made of dyed yarns is a difficult problem. This study shows how a geometric model can be developed to obtain the final colour prediction objectively. For this purpose, a woven material was divided into weft, warp and pores. Then, all parameters needed for the calculation of each colour contribution were identified. A geometrical model based on construction parameters was developed to predict the surface colour contribution of each coloured yarn in a weave surface. To validate the predicted colorimetric data, a visual assessment experiment was conducted. Then, the difference between the predicted and actual colour appearance of the weave pattern was evaluated and analysed in function of weaving structures, and weft yarns colours. For this purpose, simple woven structures (plain, twill 1/3, basket 2/2 and satin Turc) with four coloured weft yarns were used. Results show that the proposed model could correctly predict the final colour of weave designs. Therefore, the model has the potential to eliminate subjective evaluations and reduce prototype sample production by automating the process of weave/colour simulation, thereby reducing the cost and time for product development. The methods of utilization of colour in woven textiles depend upon the composition of the weave design to be woven and the structure parameters of the cloth.
Keywords: weave design; colour prediction; Jacquard CAD; dyed yarns